Effect of Education Using Booklet Media on Low Salt Diet Compliance and Fluid Restriction in Congestive Heart Failure Patients - Via Marganingsih; Dian Hudiyawati (Universitas Muhammadiyah Surakarta, 2023)
Some patients with heart failure do not adequately follow self-care instructions, including a low-salt diet and fluid restriction. This study aimed to determine the effect of education using booklet media on the average score of adherence to a low-salt diet and fluid restriction in heart failure patients. This type of research is quasi-experimental, with the number of respondents as many as 76 people at the Sebelas Maret University Hospital, Surakarta. Data collection used a non-probability sampling method with a purposive sampling technique. The difference in the average score of low-salt diet adherence pretest-posttest in the intervention group used the Wilcoxon sign rank test, the mean value was -5.868 (p = 0.001), and in the control group, the mean was 0.316 with p 0.111. The difference in the average score of adherence to fluid restriction pretest-posttest in the intervention group used the paired sample test, the mean value was -7.289 (p = 0.001), and the control group used the Wilcoxon sign rank test, the mean value was -0.263 (p 0.095). This study concludes that there is an effect of education using booklet media on the average score of adherence to a low salt diet and fluid restriction in the intervention group. There was no difference in the mean score of adherence to a low-salt diet and fluid restriction in the control group. Suggestions for further research are for further researchers to test the instrument's validity for the tool to be used.